ANALISIS GENDER NOVEL PEREMPUAN DI TITIK NOL KARYA NAWAL EL SADAWI RELEVANSINYA DENGAN PEMBELAJARAN SASTRA DI SMA - Ermawati, Titin (Educatio, 2012)
This study deals with the kinds of gender injustice issues that have been done to the woman figure in novel “Perempuan Di Titik Nol (Women At Point Zero) by Nawal El-Sadawi and its relevance to literature learning in senior high schools. Besides, the purpose of the study is to identify the image of woman figures in the novel. To achieve of the objectives above, the study used qualitative design. To analyze the data obtained, the researcher used Content Analysis. Based on the analysis, the researcher found that gender injustice happened to the leading woman figure in the novel from before, during, and after their marriage. The kinds of gender injustice are in the forms of woman marginalization, woman subordination, woman stereotype, violence againts woman and woman’s neurotic. The result of this study is useful for literature learning theoretically and practically. Theoretically, the result of this study enriches the literature’s theories and practically (especially to literature learning) it can contribute concepts for literature learning development oriented to student’s awareness of their attitudes in facing gender injustice issues in this life. Key words: gender injustice, woman image, literature learning.